ECONOMIC INEFFICIENCY AND DEBT OF TRANSPARENCY IN MEXICO - Martínez Rodríguez, María Concepción; Garcia Morales, Maria Isabel; Vera Martínez, Martin C. (Universidade de São Paulo - Programa de Pós-graduação em Integração da América Latina, 2017)
This paper analyzes the relationship of unproductive expenditure and corruption in Mexico is given. It is a descriptive exploratory study on the regulatory framework of the budget and public expenditure, exercise and transparency; describes how this works, and what were the results. Some examples are cited unproductive spending and some recommendations and conclusions outlined.